Identification of Escherichia coli Host Genes That Influence the Bacteriophage Lambda (λ) T4rII Exclusion (Rex) Phenotype. Issue 4 (1st December 2020) - Alattas, Hibah; Wong, Shirley; Slavcev, Roderick A
Abstract: Despite its historic role in evolving our understanding of modern molecular genetics, the mechanism governing the bacteriophage T4 rII exclusion (Rex) phenotype has remained a mystery for over six decades. The Rex system is thought..... Abstract: The T4r II exclusion (Rex) phenotype is the inability of T4 rII mutant bacteriophage to propagate in hosts ( Escherichia coli ) lysogenized by bacteriophage lambda (λ). The Rex phenotype, triggered by T4 rII infection of a rex + λ lysogen, results in rapid membrane depolarization imposing a harsh cellular environment that resembles stationary phase. Rex "activation" has been proposed as an altruistic cell death system to protect the λ prophage and its host from T4r II superinfection. Although well studied for over 60 years, the mechanism behind Rex still remains unclear. We have identified key nonessential genes involved in this enigmatic exclusion system by examining T4r II infection across a collection of rex + single-gene knockouts. We further developed a system for rapid, one-step isolation of host mutations that could attenuate/abrogate the Rex phenotype. For the first time, we identified host mutations that influence Rex activity and rex + host sensitivity to T4 rII infection. Among others, notable genes include tolA, ompA, ompF, ompW, ompX, ompT, lpp, mglC, and rpoS . They are critical players in cellular osmotic balance and are part of the stationary phase and/or membrane distress regulons. Based on these findings, we propose a new model that connects Rex to the σ S, σ E regulons and key membrane proteins.